Method for producing antibacterial material and antibacterial material

JP2025035617APending Publication Date: 2025-03-14KANSAI UNIVERSITY
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2023142783
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-04
Publication Date
2025-03-14

AI Technical Summary

Benefits of technology

【0013】 本発明の一実施形態に係る抗菌材料の製造方法は、優れた抗菌効果を備える抗菌材料を製造することができる。また、本発明の一実施形態に係る抗菌材料は、優れた抗菌効果を備えることができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025035617000001_ABST
    Figure 2025035617000001_ABST
Patent Text Reader

Abstract

To improve an antibacterial effect of an antibacterial material having a micro-projection by controlling morphology of the micro-projection, in the antibacterial material.SOLUTION: A method for producing an antibacterial material having a micro-projection includes a step of determining E: Young's modulus of a material constituting a micro-protrusion, I: cross-sectional secondary moment of the micro-protrusion, and L: height from a base to a tip of the micro-protrusion, so that a spring constant k=3EI / L3 of the micro-protrusion is 16.2 N / m or more.SELECTED DRAWING: Figure 5
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for producing an antibacterial material and to an antibacterial material. [Background technology]

[0002] Research has been conducted on the use of nanostructures having a nanometer-order uneven structure on the surface, in other words, nanometer-order minute protrusions, as various materials. For example, Patent Document 1 discloses an optical film having a nanometer-sized uneven structure (nanostructure) that can be used as an optical film with excellent antireflection properties, and a manufacturing method thereof.

[0003] Furthermore, as one of the materials utilizing the nanostructure, for example, the antibacterial material described in Patent Document 2 and Non-Patent Documents 1 to 3 has been developed. Here, for example, when bacteria such as Escherichia coli come into contact with the microprotrusions constituting the nanostructure of the antibacterial material, a physical action (force) is applied from the microprotrusions to the cell membrane of the bacteria. The antibacterial material utilizes the fact that the physical action damages and dissolves the cell membrane, resulting in the death of the bacteria and the exertion of an antibacterial effect. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2019-064056 A [Patent Document 2] JP 2019-72475 A [Non-patent literature]

[0005] [Non-Patent Document 1] Biophysical Journal Volume 104, 2013, 835-840. [Non-Patent Document 2] Biophysical Journal 120, 2021, 217-231. [Non-Patent Document 3] Nature Communications, Vol. 11, 2020, 1626. [Non-Patent Document 4] ACS Appl. Mate. Interfaces, Vol. 8, 2016, 14966-14974. [Non-Patent Document 5] Nature Communications, Vol. 4, 2013, 2838. Summary of the Invention [Problem to be solved by the invention]

[0006] On the other hand, in the past, there have been cases where the relationship between the strength of the antibacterial effect of the antibacterial material and the shape of the microprojections has been studied, but no unified information has been obtained. For example, while there is a document (Non-Patent Document 4) that describes that the larger the pitch, the higher the effect, there is also a document (Non-Patent Document 5) that describes that the smaller the pitch, the higher the effect. The "pitch" will be described later. Here, examples of the shape of the microprojections include the shape, size (cross-sectional area) and material of the microprojections. In addition, in the past, it was thought that antibacterial materials with pointed tips of the microprojections have a better antibacterial effect because the pressure applied to the bacteria by the microprojections is concentrated in a narrower area, making the cell membrane of the bacteria more likely to be damaged.

[0007] However, the inventors have found that the antibacterial effect of an antibacterial material with sharp tips of the microprojections is less than that of an antibacterial material with blunt tips of the microprojections, when the nanostructures have the same material, pitch, diameter and height.

[0008] Thus, the relationship between the antibacterial effect of an antibacterial material having microprotrusions and the morphology of the microprotrusions has not been found in the past.

[0009] Therefore, one aspect of the present invention aims to find a preferred shape of the microprotrusions for improving the antibacterial effect, and to improve the antibacterial effect of the antibacterial material by controlling the shape of the microprotrusions. [Means for solving the problem]

[0010] Here, recent research has revealed that the tensile force exerted by the microprotrusions on the cell membrane contributes greatly to the damage of the cell membrane. As a result of intensive research, the inventors have found that the greater the deformation (deflection) of the microprotrusions due to contact with the cells, the lower the tensile force. Furthermore, the inventors have found that when the spring constant, which is an index of the ease of deformation of the microprotrusions, is a specific value or more, the amount of deformation of the microprotrusions due to contact with the cells decreases, and a larger tensile force is applied to the cell membrane, thereby improving the antibacterial properties. Based on these findings, the inventors have found that the antibacterial effect of an antibacterial material having microprotrusions with a spring constant of a specific value or more is improved, and have arrived at the present invention.

[0011] A method for producing an antibacterial material according to one embodiment of the present invention is a method for producing an antibacterial material having microprojections, the microprojections having a spring constant k=3EI / L. 3 The method for producing an antibacterial material includes a step of determining E, I, and L so that E is 16.2 N / m or more (where E is the Young's modulus of the material constituting the microprotrusions, I is the second moment of area of ​​the microprotrusions, and L is the height from the base to the tip of the microprotrusions).

[0012] Moreover, an antibacterial material according to one embodiment of the present invention is an antibacterial material having microprojections, the microprojections having a spring constant k=3EI / L. 3 The antibacterial material has E, I, and L controlled so that the elastic modulus is 16.2 N / m or more (wherein E is the Young's modulus of the material constituting the microprotrusions, I is the second moment of area of ​​the microprotrusions, and L is the height from the base to the tip of the microprotrusions). Effect of the Invention

[0013] The method for producing an antibacterial material according to an embodiment of the present invention can produce an antibacterial material having excellent antibacterial effect. Also, the antibacterial material according to an embodiment of the present invention can have excellent antibacterial effect. [Brief description of the drawings]

[0014] [Figure 1] FIG. 2 is a schematic diagram showing how microprojections deform (flex) in an antibacterial material according to one embodiment of the present invention. [Diagram 2] Schematic diagrams showing longitudinal cross-sections of examples of the shape of microprotrusions in an antibacterial material according to one embodiment of the present invention: (a) cylindrical (no change in cross-section), (b) cylindrical (cross-section smaller at the tip), and (c) conical. [Diagram 3] 1 is a graph showing the relationship between the spring constant of the microprojections in the antibacterial materials described in the Examples and Comparative Examples of the present invention and the viable cell rate calculated from the results of a sterilization test. [Figure 4] 1 shows SEM images of the microprojections of the antibacterial materials according to (a) Example 1, (b) Example 2, (c) Comparative Example 1, (d) Comparative Example 2, and (e) Comparative Example 3 of the present invention. [Diagram 5] 1 shows SEM images of bacteria and microprojections of the antibacterial material described in Example 2 when a bactericidal test was performed using the antibacterial material. [Figure 6] 13 is an SEM image of bacteria and microprojections in the antibacterial material described in Comparative Example 3 when a bactericidal test was carried out using the antibacterial material. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0015] An embodiment of the present invention will be described in detail below. However, the present invention is not limited to this, and various modifications are possible within the described scope. For example, an embodiment obtained by appropriately combining the technical means disclosed in each of the different embodiments is also included in the technical scope of the present invention. In addition, unless otherwise specified in this specification, "A to B" representing a numerical range means "A or more, B or less". In addition, "antibacterial" described in this specification means a state in which the number of microorganisms (especially bacteria) present around the antibacterial material is reduced by killing them, or a state in which the number is not increased.

[0016] [Embodiment 1: Method for producing antibacterial material] The method for producing an antibacterial material according to one embodiment of the present invention (hereinafter also referred to as "this production method") is a method for producing an antibacterial material having microprojections, the microprojections having a spring constant k=3EI / L. 3 The method includes a step of determining E, I, and L so that E is 16.2 N / m or more (where E is the Young's modulus of the material constituting the microprotrusions, I is the second moment of area of ​​the microprotrusions, and L is the height from the base to the tip of the microprotrusions).

[0017] In short, this manufacturing method is a method for manufacturing an antibacterial material having microprotrusions with a spring constant of 16.2 N / m or more. The "spring constant" is a parameter that indicates the degree of resistance of the microprotrusions to deformation due to an external force, and the larger the value, the more resistant the microprotrusions are to deformation due to an external force. Therefore, "a spring constant of 16.2 N / m or more" means that the microprotrusions are resistant to deformation due to an external force.

[0018] In addition, the spring constant k of the micro-projection of this manufacturing method is k=3EI / L 3 The step of determining E, I, and L so that the spring constant k of the microprojections in the antibacterial material is 16.2 N / m or more is a step of controlling the spring constant k of the microprojections in the antibacterial material to be manufactured to 16.2 N / m or more. 3The step of "determining the E, the I, and the L so that the spring constant is 16.2 N / m or more" is also referred to as the "spring constant control step." In addition, in this specification, "determining the E, the I, and the L" means determining suitable ranges for the E, the I, and the L, and controlling the E, the I, and the L within the suitable ranges. In other words, the "spring constant control step" means a step of controlling the E, the I, and the L in the manufactured antibacterial material within suitable ranges to control the spring constant to 16.2 N / m or more.

[0019] When bacteria adhere to the antibacterial material, the microprotrusions of the antibacterial material and the bacteria are attracted to each other. At that time, the bacterial cells in contact with the microprotrusions deform to fit the shape of the microprotrusions, and a tensile force is applied to the cell membrane of the cells. The tensile force is a force that deforms the shape of the cells. Meanwhile, when bacteria adhere to the antibacterial material, not only the cells deform to fit the shape of the microprotrusions, but also the microprotrusions may deform to fit the shape of the cells.

[0020] When the microprotrusions are easily deformed, the degree of deformation of the microprotrusions to fit the shape of the cell is large, and the degree of deformation of the cell to fit the shape of the microprotrusions is small. Therefore, when the microprotrusions are easily deformed, the cell is less deformed and the tensile force is reduced. On the other hand, when the microprotrusions are difficult to deform, the degree of deformation of the microprotrusions to fit the shape of the cell is small, and the degree of deformation of the cell to fit the shape of the microprotrusions is large.

[0021] Therefore, when the microprotrusions are difficult to deform, the microprotrusions are less deformed, but the cells are more deformed to fit the shape of the microprotrusions, and a large tensile force is applied to the cell membrane without decreasing the tensile force. Therefore, in this case, the cell membrane of the cell is damaged and dissolved, and the cell is likely to die. The antibacterial material produced by this production method has a spring constant of 16.2 N / m or more and is difficult to deform, so it has excellent antibacterial effect. In other words, this production method can produce an antibacterial material with excellent antibacterial effect.

[0022] <Spring constant control process> A method for controlling the spring constant k by the spring constant control step will be described below.

[0023] First, as described above, when bacteria come into contact with the microprotrusions of the antibacterial material, the microprotrusions are deformed (deflected). Here, the manner in which the microprotrusions are deformed can be simplified by considering a load acting on the tip of a cantilever. Hereinafter, with reference to FIG. 1, the manner in which the microprotrusions are deformed, which can be considered as a load acting on the tip of a cantilever, will be described.

[0024] FIG. 1 is a schematic diagram showing the deformation (deflection) of the microprotrusions of the antibacterial material according to one embodiment of the present invention. The left diagram of FIG. 1 is a schematic diagram showing the shape of the microprotrusions. The center diagram of FIG. 1 is a schematic diagram showing the shape of the microprotrusions in contact with bacterial cells. As shown in the center diagram of FIG. 1, when bacteria adhere to the microprotrusions and the microprotrusions come into contact with the bacterial cells, the microprotrusions deform, for example, as shown in the diagram. The deformation can be considered as the microprotrusions being regarded as a cantilever beam, as shown in the right diagram of FIG. 1, and the cantilever beam being deformed (deflected) by a deformation amount (deflection amount) δ when a load P acts on the tip of the cantilever beam in the direction shown in the diagram. The direction shown in the diagram is a horizontal direction perpendicular to the direction from the base of the microprotrusions toward the tip of the microprotrusions.

[0025] In Fig. 1, the shape of the microprotrusions is depicted as a cylinder with an inner diameter d and a height L. However, Fig. 1 is a schematic diagram and does not accurately depict the antibacterial material of the present embodiment, and the shape of the microprotrusions may be a shape other than a cylinder.

[0026] If the deformation of the microprotrusions of the antibacterial material is regarded as the deformation when a load P is applied to the tip of the cantilever, the amount of deformation δ is expressed by the following formula (1). δ = PL 3 / 3EI··(1) (In formula (1), δ is the amount of deformation, P is the load, E is the Young's modulus of the material that constitutes the microprojection, L is the height from the base to the tip of the microprojection, and I is the second moment of area of ​​the microprojection.) Next, we transform equation (1) to create equation (2) below, which expresses the relationship between force (load) and deformation amount. Note that the symbols in equation (2) have the same meanings as those in equation (1). P = (3EI / L 3 ) × δ (2) On the other hand, when the cantilever is bent, a restoring force is generated, so Hooke's law appears to hold for the micro-protrusion, which is regarded as a cantilever. Hooke's law is expressed by the following equation (3). P = -kx (3) (In formula (3), P is the load, k is the spring constant, and x is the amount of deflection, which is a negative value.) In formula (3), x = -δ. From this and formulas (2) and (3), the following formula (4) is calculated. Note that the symbols in formula (4) have the same meanings as the symbols in formulas (1) and (3). k=3EI / L 3 (4) As shown in formula (4), the spring constant k of the microprotrusion is determined by the Young's modulus E of the material constituting the microprotrusion, the second moment of area I of the microprotrusion, and the height L from the base to the tip of the microprotrusion. Therefore, the spring constant k of the microprotrusion can be controlled by adjusting the Young's modulus E of the material constituting the microprotrusion, the second moment of area I of the microprotrusion, and the height L of the microprotrusion. Therefore, the spring constant control step is carried out by determining and adjusting the Young's modulus E of the material constituting the microprotrusion, the second moment of area I of the microprotrusion, and the height L of the microprotrusion.

[0027] (Adjustment of Young's modulus E) The Young's modulus E of the material constituting the microprotrusions is a parameter that indicates the resistance (hardness) of the material itself constituting the microprotrusions to deformation, and is a value that is specific to the material constituting the microprotrusions. Therefore, by determining the material constituting the microprotrusions, the Young's modulus E of the microprotrusions can be adjusted. When the material constituting the microprotrusions is one type of material, the Young's modulus of the material in the bulk state is publicly known, and this Young's modulus can be used as it is as the Young's modulus E of the material constituting the microprotrusions.

[0028] On the other hand, when the Young's modulus of the material constituting the microprotrusions changes from the Young's modulus of the material in the bulk state by a coating process or the like described below, the Young's modulus can be measured directly on the microprotrusions. The method for measuring the Young's modulus directly is not particularly limited, and any known method can be used. Examples of the method for measuring the Young's modulus directly include a method using an atomic force microscope, which is a type of scanning probe microscope, or a method using a nanoindenter.

[0029] (Adjustment of moment of area I) The second moment of area I of the microprotrusions is a parameter that represents the resistance to a force that bends the microprotrusions. When bacteria adhere to the microprotrusions, the microprotrusions are deformed by the force that bends the microprotrusions. Therefore, the second moment of area I of the microprotrusions represents the resistance of the shape of the microprotrusions to deformation.

[0030] The second moment of area I of the microprotrusion varies depending on parameters that define the cross-sectional area of ​​the cross-section, such as the shape of the cross-section and the length of each side that constitutes the cross-section. Here, the "cross-section" refers to the transverse section of the microprotrusion, which is a cross-section obtained by cutting the microprotrusion with a straight line parallel to the straight line that forms the base of the microprotrusion. For example, in the case of (b) of FIG. 2, the cross-section is a cross-section obtained by cutting the microprotrusion with a straight line parallel to the straight line represented by D1 in the figure (the straight line that forms the base of the microprotrusion).

[0031] The second moment of area can be calculated based on parameters that define the cross-sectional area of ​​the cross-section, using a known formula that corresponds to the shape of the cross-section. As the known formula, formulas described in the literature: Material Mechanics from the Basics (Morikita Publishing), Material Mechanics Learned from the Basics (Morikita Publishing), Material Mechanics Learned from the Basics (Morikita Publishing), etc. can be used. Furthermore, when the cross-sectional area of ​​the micro-projection varies depending on the distance from the base of the micro-projection toward the tip of the micro-projection, the second moment of area I of the micro-projection also varies depending on the degree of the variation.

[0032] For example, the second moment of area I of the (a) cylindrical (constant cross-sectional area), (b) cylindrical (cross-sectional area decreases toward the tip), and (c) conical microprotrusions shown in Figure 2 are respectively given as follows:

[0033] (a) Moment of inertia I of a cylindrical (constant cross-sectional area) microprojection When the small protrusion is cylindrical as shown in FIG. 2(a), the area second moment I is expressed by the following equation (5) using the diameter D of the circle (the inner diameter of the small protrusion) since the cross-sectional shape is circular. I=πD 4 / 64··(5) (In formula (5), I is the second moment of area, and D is the inner diameter of the micro-projection.)

[0034] (b) Moment of inertia I of a cylindrical micro-projection (cross-sectional area of ​​which decreases toward the tip) When the microprotrusion is cylindrical as shown in FIG. 2(b), the second moment of area I is expressed by the following equation (6) using the diameter D1 of the circle that is the bottom surface and the diameter D2 of the circle that is the top surface, since the cross-sectional shape is circular. I=πD2D1 3 / 64··(6) (In formula (6), I is the second moment of area, D1 is the diameter of the bottom circle, and D2 is the diameter of the top circle.)

[0035] (c) Moment of area I of a conical small protrusion When the microprotrusion is a cone-shaped microprotrusion as shown in FIG. 1(c), the diameter of the tip of the microprotrusion is described as 0 in FIG. 1(c), but in reality, the tip is a surface (upper surface) having a certain diameter. Therefore, the cone-shaped microprotrusion can actually be regarded as a cylindrical microprotrusion (with a smaller cross-sectional area at the tip) as shown in FIG. 1(b). Therefore, the area second moment I in this case is expressed by the above-mentioned formula (6) using the diameter D1 of the circle that is the bottom surface and the diameter D2 of the circle that is the top surface, similar to the area second moment of the cylindrical microprotrusion (with a smaller cross-sectional area at the tip) in (b) described above.

[0036] In addition, examples of shapes having a cross section other than a circle include, for example, a prism and a pyramid. Although the following description will be given using a square prism and a triangular prism as examples of a prism, the present invention also includes shapes having a cross section other than these that are polygonal (for example, a square pyramid and a triangular pyramid). Examples of the microprotrusions having a square prism shape include, for example, microprotrusions having the shapes listed below. (d) A microprojection in the shape of a rectangular prism, with a square cross section and a constant cross-sectional area; (e) A microprotrusion in the shape of a rectangular prism, with a rectangular cross section and a constant cross-sectional area.

[0037] Examples of the triangular prism-shaped microprotrusions include microprotrusions having the shapes shown below. (f) A tiny protrusion in the shape of a triangular prism, with a triangular cross section and a constant cross-sectional area.

[0038] The area second moment I of these shapes is as shown below.

[0039] (d) The second moment of area I of a small protrusion in the shape of a rectangular prism with a square cross section and a constant cross-sectional area The area second moment I of the minute protrusion is expressed by the following formula (7) using the length a of one side of the square that is the cross section. I=a 4 / 12··(7) (In formula (7), I is the second moment of area, and a is the length of one side of the square cross section.) (e) The second moment of area I of a small protrusion in the shape of a rectangular prism with a rectangular cross section and a constant cross-sectional area The area second moment I of the minute protrusion is expressed by the following formula (8) using the length b of the long side and the length c of the short side of the rectangle that is the cross section. I=cb 3 / 12··(8) (In formula (8), I is the second moment of area, b is the length of the long side of the rectangular cross section, and c is the length of the short side of the rectangular cross section.)

[0040] (f) Moment of inertia I of a small protrusion that is a triangular prism, has a triangular cross section, and has a constant cross-sectional area The second moment of area I of the small protrusion is expressed by the following equation (9) using the length e of the longest side (base) of the triangle that is the cross section and the length f of the perpendicular line extending from the base to the vertex angle opposite the base. I=ef 3 / 36··(9) (In formula (9), I is the second moment of area, e is the length of the base of the triangle that is the cross section, and f is the length of the perpendicular line extending from the base of the triangle that is the cross section to the apex angle of the base.) As described above, the area second moment I of the microprotrusion varies depending on parameters that define the cross-sectional area of ​​the cross-section, such as the shape of the cross-section, the presence or absence of variation in the cross-sectional area, the degree of variation if the cross-sectional area varies, and the length of each side that constitutes the cross-section. The shape of the cross-section, the presence or absence of variation in the cross-sectional area, and the degree of variation if the cross-sectional area varies are determined by the shape of the microprotrusion itself. Therefore, the area second moment I of the microprotrusion can be adjusted by adjusting parameters that define the cross-sectional area of ​​the cross-section, such as the shape of the microprotrusion and the length of each side that constitutes the cross-section. In detail, "adjusting the shape of the microprotrusion and the parameters that define the cross-sectional area of ​​the cross-section" means that the parameters are determined after the shape of the microprotrusion is determined. Examples of the parameters include the following parameters.

[0041] (i) When the microprotrusion is a cylindrical microprotrusion (having a constant cross-sectional area), the diameter of the circle that is the cross-section, i.e., the inner diameter of the microprotrusion; (ii) In the case where the microprotrusion is a cylindrical (cross-sectional area is smaller toward the tip) or conical microprotrusion, the diameter of the circle that is the bottom surface and the diameter of the circle that is the top surface; (iii) in the case where the microprotrusion is a rectangular prism having a square cross section and a rectangular parallelepiped shape with a constant cross-sectional area, the length of one side of the square cross section; (iv) in the case where the microprotrusion is a quadrangular prism, has a rectangular cross section, and is a rectangular parallelepiped with a constant cross-sectional area, the lengths of the long and short sides of the rectangular cross section; (v) in the case where the microprotrusion is a rectangular prism having a square cross section and a rectangular parallelepiped shape in which the cross-sectional area decreases toward the tip, or a square pyramid having a square cross section, the length of one side of the square bottom surface and the length of one side of the square top surface; (vi) In the case where the microprotrusion is a rectangular prism having a rectangular cross section and a rectangular parallelepiped shape with the cross-sectional area decreasing toward the tip, or a square pyramid having a rectangular cross section, the lengths of the long and short sides of the rectangular bottom surface and the lengths of the long and short sides of the rectangular top surface; (vii) in the case where the microprotrusion is a triangular prism having a triangular cross section and a constant cross-sectional area, the length of the base of the triangle that is the cross section and the length of a perpendicular line extending from the base to the apex angle of the base; (viii) In the case where the microprotrusion is a triangular prism having a triangular cross section and a cross-sectional area that decreases toward the tip, or a triangular pyramid having a triangular cross section, the length of the base of the triangle that is the bottom surface and the length of the perpendicular line extending from the base to the apex angle of the base, and the length of the base of the triangle that is the top surface and the length of the perpendicular line extending from the base to the apex angle of the base. Generally, the second moment of area can be calculated by multiplying the cross-sectional area by the square of the distance from the neutral axis, but when calculating the second moment of area for various complex shapes, it can be calculated by methods generally known in the fields of material engineering and / or structural mechanics. For example, the second moment of area for each shape can be calculated by adding and subtracting them, and when the cross section deviates from the neutral axis, the second moment of area can be calculated using the "parallel axis theorem."

[0042] By appropriately adjusting the manufacturing conditions in this manufacturing method, the parameters that define the shape of the cross section and the cross-sectional area of ​​the cross section can be adjusted. For example, when the antibacterial material is manufactured by a method using a mold having nanoholes, which will be described later, the preparation conditions of the mold are adjusted to adjust the shape and hole diameter of the nanoholes. This allows the parameters that define the shape of the cross section and the cross-sectional area of ​​the cross section to be adjusted.

[0043] (Adjusting the height L from the base to the tip of the microprojection) The height L from the base to the tip of the microprotrusions can be adjusted by appropriately adjusting the manufacturing conditions in the present manufacturing method, as well as the parameters that define the shape and cross-sectional area of ​​the microprotrusions. For example, when the antibacterial material is manufactured by a method using a mold having nanoholes, which will be described later, the height L can be adjusted by adjusting the preparation conditions of the mold to adjust the depth of the nanoholes.

[0044] (summary) As described above, in this manufacturing method, E, I, and L can be determined by appropriately adjusting the parameters that define the material constituting the microprotrusions, the shape of the microprotrusions, and the cross-sectional area of ​​the cross section.

[0045] As a result, this manufacturing method can produce an antibacterial material with excellent antibacterial effect, which is provided with microprotrusions having a spring constant k of 16.2 N / m or more.

[0046] <Specific methods for producing antibacterial materials> The specific means for carrying out this manufacturing method is not particularly limited as long as it is possible to manufacture an antibacterial material having microprojections with a spring constant of 16.2 N / m or more, and any known method for manufacturing an antibacterial material having microprojections can be adopted. As the method, for example, a nanoimprint (NIL) method can be adopted.

[0047] The NIL method is an advanced version of embossing technology, dramatically increasing its resolution to the nano-order. Specifically, it is a method in which a mold with a nano-order uneven pattern is pressed against a polymer film formed on a substrate, transferring the uneven pattern. Currently, there are three known NIL methods: thermal nanoimprinting, UV nanoimprinting, and microcontact printing. The mold with the nano-order uneven pattern is a mold that has nano-level holes (called nanoholes).

[0048] The thermal nanoimprinting method involves heating a mold and a resin or the like to be molded at a predetermined temperature while applying a predetermined pressure to the mold and holding the resin in such a way that the resin is deformed (molded) and the fine shape of the mold's surface in contact with the resin is transferred to the resin. The predetermined temperature can be a temperature at which the resin or the like to be molded is softened. The thermal nanoimprinting method has the advantage that it can be directly processed into various materials as long as they are materials that are softened by heating. In addition to the above advantages, the nanoimprinting method has the advantage that the microprojections and the base (substrate) are made of the same material and are integrated, so that there are no connecting parts. Therefore, when the NIL method is adopted, it is preferable to adopt the thermal nanoimprinting method out of the three types.

[0049] The predetermined temperature (heating temperature) is set with reference to the glass transition temperature (Tg) of the resin, etc. Molding is often performed at a temperature several tens of degrees Celsius higher than the glass transition temperature of the molding target, and the glass transition temperature of resins that are typical molding targets used in thermal nanoimprinting is about 100 to 200 degrees Celsius.

[0050] Thus, in the thermal nanoimprinting, the resin is heated to above its glass transition temperature, and while maintaining the temperature, pressure is applied to mold the resin, and the fine shape of the mold is transferred to the resin. In order to transfer the fine shape to the resin with high accuracy, the temperature and load during molding as well as the pressure holding time are important, and it is preferable to take a long pressure holding time to transfer a high aspect ratio structure with high accuracy. Furthermore, it is also possible to transfer a pattern with ultra-high accuracy by reducing the pressure at the contact portion between the mold and the resin. In addition, when releasing the resin from the mold after the transfer, in order to suppress deformation of the resin after release, it is preferable to release the resin after cooling the temperature of the resin to below the glass transition temperature.

[0051] The mold has nanoholes. The method for preparing the mold is not particularly limited as long as it is possible to prepare a mold having desired nanoholes, and any known preparation method can be used. For example, a method using anodized alumina (AAO) can be mentioned as an example of the method.

[0052] The AAO is an oxide film formed on the surface of an aluminum (Al) plate by applying a certain voltage in an acidic electrolyte using an aluminum plate as an anode and a cathode containing a material selected from platinum (Pt) and carbon (C). It is known that nanoholes are self-ordered depending on the anodization conditions, and a nanohole structure can be easily produced. Since this oxide film is hard, the Al plate on which the oxide film is formed on the surface can be used as a mold. The cell diameter (corresponding to pitch) and hole diameter of the formed film depend on the applied voltage, as well as the type, concentration, and temperature of the acidic electrolyte, and can be controlled on the order of several tens to several hundreds of nm depending on the conditions. Similarly, the hole depth can be controlled because it depends on the temperature of the acidic electrolyte, the applied current value, the application time of the voltage, etc. In addition, since the formed oxide film can be etched with phosphoric acid, it is also possible to expand the hole diameter without changing the pitch.

[0053] As described in detail in the following references, when the applied voltage is high, the pitch of the nanoholes tends to become large. When the type of the acidic electrolyte is oxalic acid, the pitch of the nanoholes can be controlled to about 100 to 200 nm. The obtained hole diameter is about 30 nm, but the hole diameter can be easily enlarged by immersing the nanoholes in phosphoric acid. In this case, the hole diameter can be enlarged as the immersion time is increased. When the voltage is applied for a long time, the depth of the holes becomes deeper. [References] T. Kikuchi, “Development of novel functional aluminum materials based on surface nanostructures,” Japan Institute of Light Metals, vol. 68, no. 4, pp. 211-218, 2018.

[0054] When actually carrying out the thermal nanoimprinting, it is preferable to carry out the thermal nanoimprinting by sequentially carrying out the following steps (1) to (5) on an Al plate. (1) Electrolytic polishing treatment, (2) First stage anodizing, (3) Selective etching of AAO; (4) Second stage anodizing, (5) Nanohole enlargement treatment (hereinafter referred to as "widening").

[0055] The widening can be performed by immersing the nanoholes in a phosphoric acid solution. The method consisting of the steps (1) to (5) is called a two-step anodization method, and is a method that can form nanoholes with high regularity. In addition, the nanoholes created by the two-step anodization method have very high verticality. On the other hand, by repeatedly performing the steps (4) and (5) in a short time, a cone-shaped inverse pattern with a small diameter at the bottom of the hole and a large diameter at the inlet of the hole can be obtained. When the mold having the cone-shaped inverse pattern is used to transfer the resin, an antibacterial material having cone-shaped microprojections can be obtained. When the mold having the cylindrical pattern is used to transfer the resin, an antibacterial material having cylindrical microprojections can be obtained. The microprojections mean a fine structure on the order of nanometers to micrometers, and in the present invention, for example, microprojections having the physical property values ​​described in <Physical Properties of Microprojections of Antibacterial Material> described later. "Nanometer order" refers to more than 0 nm and less than 1000 nm, and "micrometer order" refers to 1 μm or more and less than 1000 μm.

[0056] <Process for coating the surface of the microprojections with an inorganic material> The present manufacturing method may further include a step of coating the surface of the microprotrusions with an inorganic material. The step of further including this step means that a material coated with an inorganic material is selected as the material constituting the microprotrusions. Thus, this step is included in the above-mentioned spring constant control step, particularly the step of determining the Young's modulus of the material constituting the microprotrusions.

[0057] Here, the inorganic material generally has a higher Young's modulus than a resin material, and therefore, when the above-mentioned step is further included, the microprotrusions are coated with a material having a high Young's modulus, so that the Young's modulus E of the material constituting the microprotrusions can be improved.

[0058] The inorganic material is not particularly limited, and may be, for example, one or more selected from the group consisting of single crystal silicon (Si) with a Young's modulus of 193 GPa, silicon dioxide (SiO2) with a Young's modulus of about 72 GPa, titanium dioxide (TiO2) with a Young's modulus of about 300 GPa, and alumina (Al2O3) with a Young's modulus of about 350 GPa.

[0059] The coating method for carrying out the above-mentioned step is not particularly limited, and any known method can be used. Examples of the method include atomic layer deposition (ALD), sputtering, ion plating, CVD, and electroless plating, and ALD is preferred because it can control the thickness at the atomic level.

[0060] The coating method using the ALD can be a method based on the literature (M. Degai et al., Thin Solid Films, vol. 525, 73-76 (2012)). This method uses tris(dimethylamino)silane and plasma-excited water vapor as raw materials, and deposits SiO2 on the surface of the micro-projections to coat them.

[0061] The larger the thickness of the coating layer formed from the inorganic material, the higher the Young's modulus E of the material constituting the microprotrusions, and the greater the spring constant k of the microprotrusions, which is preferable. From this viewpoint, the thickness of the coating layer formed from the inorganic material is preferably 1 nm to 100 nm, more preferably 5 nm to 50 nm, and even more preferably 10 nm to 20 nm.

[0062] <Shape of micro-projections> The shape of the microprotrusions is not particularly limited, and may be, for example, one or more shapes selected from the group consisting of the above-mentioned cylinders, square prisms, triangular prisms, cones, pyramids, and triangular pyramids, and is preferably one or more shapes selected from the group consisting of cylinders, cones, and prisms. In addition, microprotrusions with a blunt tip are less likely to deform when a load is applied to the tip compared to microprotrusions with a sharp tip, and therefore the spring coefficient is larger. Therefore, from the viewpoint of easily controlling the spring coefficient to a range of 16.2 N / m or more, it is more preferable that the shape of the microprotrusions is one or more shapes selected from the group consisting of cylinders, square prisms, triangular prisms, and other prisms. In this specification, the cylinder includes not only cylinders with a constant cross-sectional area, generally called cylinders, but also cylinders with a cross-sectional area that varies with height, such as cylinders with a cross-sectional area that decreases toward the tip, generally called truncated cones. Similarly, the prism includes not only prisms with a constant cross-sectional area, generally called prisms, but also prisms with a cross-sectional area that varies with height, such as prisms with a cross-sectional area that decreases toward the tip, generally called truncated pyramids.

[0063] The microprotrusions contained in the antibacterial material may all have the same shape, or may have different shapes. For example, some of the microprotrusions contained in the antibacterial material may have a cylindrical shape, while other microprotrusions may have a rectangular prism shape. The height and / or diameter of each microprotrusion may be different.

[0064] <Materials that make up the microprojections> The material constituting the micro-projections is not particularly limited, but it is preferable to use a resin material. For example, the material may be one or more selected from the group consisting of cycloolefin polymer (COP polymer), polyolefin, polytetrafluoroethylene (PTFE), polyimide, polyether ether ketone (PEEK), acrylic, polycarbonate (PC), polyethylene terephthalate (PET), polyamide, polyacetal, silicone resin which is a resin having a siloxane bond, and polyurethane, and it is preferable to include a COP polymer. It is also preferable to use a silicon (Si) material.

[0065] Here, in this manufacturing method, a case will be considered in which the moment of inertia I of the area of ​​the minute protrusion and the height L from the base to the tip of the minute protrusion are determined first.

[0066] In this case, when the above I and L are adopted, a material having a Young's modulus E such that the spring constant k of the minute protrusion is 16.2 N / m or more may be selected as the material constituting the minute protrusion.

[0067] Conversely, consider a case where the Young's modulus E of the material constituting the minute protrusion is determined first. In this case, I and L should be determined so that the spring constant k of the minute protrusion is 16.2 N / m or more when the Young's modulus E is adopted.

[0068] <Materials that make up antibacterial materials> The material constituting the portion of the antibacterial material other than the microprojections, i.e., the base (substrate) of the microprojections, may be the same as or different from the material constituting the microprojections. The material constituting the base (substrate) of the microprojections is not particularly limited, and the materials given as examples of the material constituting the microprojections above can be used.

[0069] <Physical properties of antibacterial material microprojections> (pitch) The antibacterial material may have two or more microprojections. When the antibacterial material has two or more microprojections, the pitch between adjacent microprojections of the antibacterial material is preferably 20 nm or more, more preferably 50 nm or more, and even more preferably 100 nm or more. The pitch is preferably 5 μm or less, more preferably 2 μm or less, and even more preferably 500 nm or less. The pitch means the center-to-center distance between adjacent microprojections. The center-to-center distance is the distance between a perpendicular line drawn from the midpoint of the straight line forming the base of the microprojection in the longitudinal section of the microprojection to the tip of the microprojection and a similar perpendicular line in another microprojection adjacent to the microprojection. Taking (b) of FIG. 2 as an example, it is the distance between a perpendicular line drawn from the midpoint of the straight line represented by D1 in the figure (the straight line forming the base of the microprojection) to the tip of the microprojection shown in (b) of FIG. 2 and a perpendicular line drawn similarly in another microprojection (not shown) adjacent to the microprojection.

[0070] (density) The density of the microprojections in the antibacterial material is 10,000 pcs / mm 2 It is preferable that the number of particles is 100,000 or more per mm. 2 More preferably, it is 500,000 pieces / mm 2 It is more preferable that the density is 1,000,000,000 pieces / mm or more. 2 It is preferable that the number of particles is 500,000,000 / mm or less. 2 More preferably, it is 50,000,000 pieces / mm or less. 2 By having the density within these ranges, bacteria can come into contact with a sufficient number of microprotrusions, thereby further improving the antibacterial effect of the antibacterial material.

[0071] (Height from base to tip L) The height L from the base to the tip of the microprotrusion, together with the Young's modulus E of the material constituting the microprotrusion and the moment of inertia I of the area of ​​the microprotrusion, may be appropriately determined so that the spring constant k is 16.2 N / m or more. The height L may be, for example, 10 nm or more, preferably 30 nm or more, and more preferably 50 nm or more. The height L may be 5 μm or less, preferably 1 μm or less, and more preferably 500 nm or less.

[0072] (Parameter that defines the cross-sectional area) The parameters that define the cross-sectional area of ​​the microprotrusions, together with the Young's modulus E of the material that constitutes the microprotrusions, the height L from the base to the tip of the microprotrusions, and the shape of the microprotrusions, may be appropriately determined so that the spring constant k is 16.2 N / m or more. The parameters may be within the ranges shown below, for example.

[0073] (i) When the shape of the microprotrusions is cylindrical (with a constant cross-sectional area), the diameter of the circle that is the cross section may be 10 nm or more, preferably 30 nm or more, and more preferably 50 nm or more, and the diameter may be 3 μm or less, preferably 1 μm or less, and more preferably 500 nm or less.

[0074] (ii) When the shape of the microprotrusion is cylindrical (the cross-sectional area is smaller toward the tip) or conical, the diameter of the circle that is the base may be 10 nm or more, preferably 30 nm or more, and more preferably 50 nm or more, and the diameter of the circle that is the base may be 3 μm or less, preferably 1 μm or less, and more preferably 500 nm or less. The diameter of the circle that is the upper surface may be 5 nm or more, preferably 10 nm or more, and more preferably 30 nm or more, and the diameter of the circle that is the upper surface may be 2 μm or less, preferably 900 nm or less, and more preferably 450 nm or less.

[0075] (iii) When the shape of the microprotrusion is a rectangular prism with a square cross section and a rectangular parallelepiped shape with a constant cross-sectional area, the length of one side of the square may be 10 nm or more, preferably 30 nm or more, and more preferably 50 nm or more, and the length of one side of the square may be 3 μm or less, preferably 1 μm or less, and more preferably 500 nm or less.

[0076] (iv) When the shape of the microprotrusion is a square prism, the cross section is rectangular, and the cross section is a rectangular parallelepiped with a constant cross-sectional area, the length of the long side of the rectangle may be 10 nm or more, preferably 30 nm or more, and more preferably 50 nm or more, and the length of the long side of the rectangle may be 3 μm or less, preferably 1 μm or less, and more preferably 500 nm or less. The length of the short side of the rectangle may be 10 nm or more, preferably 30 nm or more, and more preferably 50 nm or more, and the length of the short side of the rectangle may be 3 μm or less, preferably 1 μm or less, and more preferably 500 nm or less.

[0077] (v) When the shape of the microprotrusion is a rectangular prism with a square cross section and a rectangular parallelepiped shape with the cross section area decreasing toward the tip, or when the shape is a square pyramid with a square cross section, the length of one side of the square base may be 10 nm or more, preferably 30 nm or more, and more preferably 50 nm or more. Also, the length of one side of the square may be 3 μm or less, preferably 1 μm or less, and more preferably 500 nm or less. The length of one side of the square upper surface may be 5 nm or more, preferably 10 nm or more, and more preferably 30 nm or more, and the length of one side of the square upper surface may be 2 μm or less, preferably 900 nm or less, and more preferably 450 nm or less.

[0078] (vi) When the shape of the microprotrusion is a square prism, the cross section is a rectangle, and the cross section area is smaller toward the tip, or when the shape is a square pyramid and the cross section is a rectangle, the length of the long side of the rectangle that is the bottom surface may be 10 nm or more, preferably 30 nm or more, and more preferably 50 nm or more. The length of the long side of the rectangle that is the bottom surface may be 3 μm or less, preferably 1 μm or less, and more preferably 500 nm or less. The length of the short side of the rectangle that is the bottom surface may be 10 nm or more, preferably 30 nm or more, and more preferably 50 nm or more. The length of the short side of the rectangle that is the bottom surface may be 3 μm or less, preferably 1 μm or less, and more preferably 500 nm or less. The length of the long side of the rectangle that is the upper surface may be 5 nm or more, preferably 10 nm or more, and more preferably 30 nm or more. The length of the long side of the rectangle that is the upper surface may be 2 μm or less, preferably 900 nm or less, and more preferably 450 nm or less. The length of the short side of the rectangle that is the upper surface may be 5 nm or more, preferably 10 nm or more, and more preferably 30 nm or more. The length of the short side of the rectangle that is the upper surface may be 2 μm or less, preferably 900 nm or less, and more preferably 450 nm or less.

[0079] (vii) When the shape of the microprotrusion is a triangular prism with a triangular cross section and a constant cross-sectional area, the length of the base of the triangle may be 10 nm or more, preferably 30 nm or more, and more preferably 50 nm or more. The length of the base of the triangle may be 3 μm or less, preferably 1 μm or less, and more preferably 500 nm or less. The length of a perpendicular line extending from the base of the triangle to the apex angle opposite the base may be 5 nm or more, preferably 10 nm or more, and more preferably 30 nm or more, and the length of the perpendicular line may be 2 μm or less, preferably 900 nm or less, and more preferably 450 nm or less.

[0080] (viii) When the shape of the microprotrusion is a triangular prism with a triangular cross section and a cross-sectional area that decreases toward the tip, or when the shape is a triangular pyramid with a triangular cross section, the length of the base of the triangle, which is the bottom surface, may be 10 nm or more, preferably 30 nm or more, and more preferably 50 nm or more. The length of the base of the triangle may be 3 μm or less, preferably 1 μm or less, and more preferably 500 nm or less. The length of a perpendicular line extending from the base of the triangle to the apex angle opposite the base may be 5 nm or more, preferably 10 nm or more, and more preferably 30 nm or more, and the length of the perpendicular line may be 2 μm or less, preferably 900 nm or less, and more preferably 450 nm or less. The length of the base of the triangle that is the upper surface may be 10 nm or more, preferably 30 nm or more, and more preferably 50 nm or more, and the length of the base of the triangle may be 3 μm or less, preferably 1 μm or less, and more preferably 500 nm or less. The length of a perpendicular line extending from the base of the triangle that is the upper surface to the apex angle of the base may be 5 nm or more, preferably 10 nm or more, and more preferably 30 nm or more, and the length of the perpendicular line may be 2 μm or less, preferably 900 nm or less, and more preferably 450 nm or less.

[0081] [Embodiment 2: Antibacterial Material] An antibacterial material according to one embodiment of the present invention (hereinafter also referred to as "the present antibacterial material") is an antibacterial material having microprojections, the microprojections having a spring constant k=3EI / L. 3 The antibacterial material has E, I, and L controlled so that the elastic modulus is 16.2 N / m or more (wherein E is the Young's modulus of the material constituting the microprotrusions, I is the second moment of area of ​​the microprotrusions, and L is the height from the base to the tip of the microprotrusions).

[0082] In short, this antibacterial material is an antibacterial material having microprotrusions with a spring constant of 16.2 N / m or more. As shown in the above section [Embodiment 1: Manufacturing method of antibacterial material], an antibacterial material with a spring constant of 16.2 N / m or more is difficult to deform, and therefore has excellent antibacterial effect. Therefore, this antibacterial material has excellent antibacterial effect.

[0083] The present antibacterial material is an antibacterial material that can be produced by the present production method. Here, the description of the antibacterial material in the above section "Embodiment 1: Production method of antibacterial material" is incorporated by reference as the description of the present antibacterial material.

[0084] The antibacterial material has a spring constant k of the microprojections of 3EI / L. 3 It is sufficient that the antibacterial material has microprotrusions (hereinafter referred to as "microprotrusions of the present invention") whose E, I, and L are controlled so that the elastic modulus is 16.2 N / m or more. The antibacterial material may further have microprotrusions that do not correspond to the microprotrusions of the present invention, so long as the effect of the present invention is not impaired. In order to further improve the antibacterial effect of the antibacterial material, it is preferable that the proportion of microprotrusions that correspond to the microprotrusions of the present invention among all the microprotrusions is large, and it is particularly preferable that all the microprotrusions are microprotrusions that correspond to the microprotrusions of the present invention.

[0085] The present invention is not limited to the above-described embodiments, and various modifications are possible within the scope of the claims. Embodiments obtained by appropriately combining the technical means disclosed in different embodiments are also included in the technical scope of the present invention.

[0086] 〔summary〕 The present invention includes the following aspects. <1> 1. A method for producing an antimicrobial material with microprojections, comprising: The spring constant of the microprojection is k=3EI / L. 3A method for producing an antibacterial material, comprising a step of determining E, I, and L so that E is 16.2 N / m or more (where E is the Young's modulus of a material constituting the microprotrusions, I is the second moment of area of ​​the microprotrusions, and L is the height from the base to the tip of the microprotrusions). <2> The shape of the microprojections is one or more selected from the group consisting of cylinders, prisms, cones, and pyramids; <1> A method for producing the antibacterial material described in claim 1. <3> The shape of the microprojections is one or more selected from the group consisting of cylinders, cones and prisms; <2> A method for producing the antibacterial material described in claim 1. <4> Further comprising the step of coating the surface of the microprojections with an inorganic material. <1> ~ <3> 13. A method for producing an antibacterial material according to any one of the above. <5> 1. An antimicrobial material comprising microprojections, The spring constant of the microprojection is k=3EI / L. 3 The antibacterial material, in which E, I, and L are controlled so that the elastic modulus is 16.2 N / m or more (wherein E is the Young's modulus of the material constituting the microprojections, I is the second moment of area of ​​the microprojections, and L is the height from the base to the tip of the microprojections). <6> The shape of the microprojections is one or more selected from the group consisting of cylinders, prisms, cones, and pyramids; <5> The antibacterial material according to claim 1. <7> The shape of the microprojections is one or more selected from the group consisting of a cylinder, a cone, and a prism. <6> The antibacterial material according to claim 1. <8> The surface of the microprojections is coated with an inorganic material. <5> ~ <7> 13. An antibacterial material according to any one of the above. EXAMPLES

[0087] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples.

[0088] [Measurement method] The physical properties of the antibacterial materials produced in the Examples and Comparative Examples were measured and evaluated by the methods described below.

[0089] <Bactericidal test> A bactericidal test was carried out by staining the DNA inside the bacteria using DNA staining reagents SYTO 9 and PI (propidium iodide) and evaluating the damage to the cell membrane to determine whether the bacteria were alive or dead. Based on the results of the bactericidal test, the antibacterial effect of the antibacterial material was evaluated. This method is called a Live / Dead Assay and is widely used to evaluate the antibacterial effect of antibacterial materials. This evaluation method is effective because after the bacteria attach to the microprojections (nanostructures) of the antibacterial material, membrane damage occurs due to physical effects as described above. In the case of bacteria, which are simple organisms, membrane damage causes various substances necessary for survival to flow out of the cells, making them unable to survive. Therefore, in the bactericidal test, it was interpreted that if membrane damage occurs, the bacteria will die.

[0090] Here, SYTO 9 is a staining substance that is cell membrane permeable, and stains DNA green regardless of whether the cell membrane is damaged or not. On the other hand, PI is not cell membrane permeable, so it enters the cell only when the cell membrane is damaged and stains DNA red. Furthermore, since PI has a higher affinity for DNA than SYTO 9, when the cell membrane is damaged, DNA is mainly stained by PI. Therefore, when the cell membrane is not damaged, it is stained with SYTO 9 (green), and when the cell membrane is damaged, it is stained with PI (red). Therefore, the bacteria stained with SYTO 9 are considered to be live bacteria, and the bacteria stained with PI are considered to be dead bacteria, and the viable bacteria rate was calculated using the following formula (13). Then, the antibacterial effect of the antibacterial material was evaluated based on the viable bacteria rate. Viable cell rate = number of green cells ÷ total number of cells × 100 [%] (13) Here, the total number of bacteria is the sum of the number of green bacteria and the number of red bacteria. Specifically, E. coli was cultured and stained, and the viable cell rate was calculated by the following method, and a sterilization test was performed on the antibacterial materials produced in the Examples and Comparative Examples. Based on the results, the antibacterial effects of the antibacterial materials were evaluated.

[0091] First, E. coli wild-type strain (RP437 strain) stored at -80°C was thawed. 20 μL of E. coli was obtained from the thawed E. coli wild-type strain, suspended in Luria-Bertani medium (LB medium) (2 mL), and cultured for 3 hours under conditions of 30°C and 170 rpm in a bioshaker (TAITEC Co., Ltd., BR-23FP) to obtain a bacterial liquid. 1 mL of the obtained bacterial liquid was dispensed into a microtube and centrifuged at 10,000 rpm for 2 minutes. 1 mL of phosphate buffered saline (PBS(-): Phosphate Buffered Saline) was added to the microtube from which only the supernatant LB medium had been removed, and the microtube was lightly suspended, and the bacterial liquid was diluted with PBS(-) so that the turbidity of the bacterial liquid became OD600=0.1.

[0092] A certain amount (30 μL) of the obtained bacterial liquid was dropped onto the micro-projections of the sample to be evaluated, and a sterilized slide glass was placed on top of it to prevent it from drying, and it was left standing at 25° C. in a light-shielded state for 18 hours. Here, the sample to be evaluated is the antibacterial material produced in the examples and comparative examples. Next, the slide glass was gently removed, and the bacterial liquid remaining on the sample to be evaluated was sucked up.

[0093] Next, the sample to be evaluated was fixed to a slide glass with double-sided tape so that it could be fixed to a fluorescent microscope. Next, 30 μL of a staining solution was dropped onto the sample to be evaluated. The staining solution was prepared by mixing SYTO 9 (1.0 μL) and PI (1.5 μL) in PBS(-) (500 μL).

[0094] Furthermore, double-sided tape was attached to both ends of the sample to be evaluated on which the staining solution was dropped, and a glass slide was attached from above. This double-sided tape served as a spacer (thickness: 0.12 mm) and also served to prevent the bacterial solution from moving significantly due to external factors. Ten minutes after covering with the glass slide, the fluorescent images of E. coli attached to the surface of the sample to be evaluated were observed using a fluorescent microscope at five points per sample to be evaluated.

[0095] From the fluorescent image of E. coli, the number of live bacteria stained green (E. coli) and the number of dead bacteria stained red (E. coli) were counted. The live bacteria rate was calculated and evaluated based on the formula (13) using the counted number of live bacteria and the number of dead bacteria.

[0096] <Observation of microscopic protrusions of antibacterial materials> The surface (front side) of the antibacterial materials produced in the Examples and Comparative Examples on which the microprotrusions were present was observed using a scanning electron microscope (SEM) (manufactured by JEOL Ltd., product name: JSM7500F) at an acceleration voltage of 5 kV to obtain SEM images. Based on the obtained SEM images, the shape, pitch, cross-sectional diameter (when the microprotrusions were cylindrical), bottom diameter, top diameter (when the microprotrusions were conical), and height from base to tip were measured using software attached to the device.

[0097] Example 1

[0098] <Preparation of mold> A mold with a nanohole structure was prepared using a method called hard anodization. Hard anodization is a method of applying a high voltage to an aluminum (Al) plate in a sufficiently cooled state to create self-organization and highly regular nanoholes, and the oxide film grows quickly.

[0099] First, an aluminum plate (Al plate) (purity 99.99%) was subjected to electrolytic polishing. The electrolytic treatment solution used was a mixture of perchloric acid and ethanol in a volume ratio of 1:4. The voltage was 10 V. The Al plate after electrolytic polishing was subjected to a first stage of anodization (hereinafter referred to as "first anodization") under the conditions shown below. The first anodization was performed by applying a voltage under the conditions shown below in an acid electrolyte with the Al plate after electrolytic polishing as the anode and Pt as the cathode to form an oxide film on the Al plate.

[0100] (Conditions for the first anodizing) Mode of voltage application: The applied voltage was set to 40 V at the start of the first anodization, and the voltage was applied for 8 minutes while keeping the applied voltage constant (40 V). After that, the applied voltage was increased to 140 V at a rate of 12.5 mV / s per unit time, and then the voltage application was continued while keeping the applied voltage constant (140 V) until the time from the start of voltage application reached 1.5 h. Acid electrolyte type: Oxalic acid Acid electrolyte concentration: 0.3M Acid electrolyte temperature: 0℃ Next, the obtained Al plate was immersed in a mixed solution of phosphoric acid (H3PO4 6 wt%) and chromium VI oxide (CrO3 1.8 wt%) for 15 minutes to perform AAO selective etching (hereinafter referred to as "AAO etching"). After that, the obtained Al plate was subjected to a second stage of anodization (hereinafter referred to as "second anodization"). The second anodization was performed in the same manner as the first anodization, except that the Al plate after the AAO etching was used as the anode instead of the Al plate after the electrolytic polishing treatment, and the manufacturing conditions were changed to the conditions shown below.

[0101] (Conditions for the second anodizing) Voltage application mode: A constant voltage of 120V was applied. Acid electrolyte type: phosphoric acid Acid electrolyte concentration: 0.29M Acid electrolyte temperature: 10℃ Voltage application time: 5 minutes Nanoholes were formed on the Al plate obtained by the second anodization. The Al plate was then immersed in phosphoric acid and subjected to a hole enlargement treatment (widening) of the nanoholes at 34°C to prepare a mold. At this time, the holes formed in the mold were cylindrical, with a hole pitch of about 300 nm, a hole diameter of about 150 nm, and a hole depth of about 150 nm.

[0102] <Preparation of antibacterial material> A cycloolefin polymer (COP) film (ZF16: Tg = 163 ° C.) manufactured by Zeon Corporation was prepared. The Young's modulus of the cycloolefin polymer resin constituting the COP film was 2 GPa. The mold was heat-pressed against the COP film so that the surface of the mold on which the nanoholes were formed was in contact with the COP film. The heat-pressing was carried out for 10 minutes using a small electric press G-12RS type (Orihara Manufacturing Co., Ltd.) under conditions of temperature: 180 ° C. and pressure: 4.2 MPa. In this way, thermal nanoimprinting was carried out to produce an antibacterial material in which microprojections were generated on the COP film. This antibacterial material is referred to as antibacterial material 1.

[0103] The shape of the microprotrusions of antibacterial material 1 was measured using SEM by the method described above. The obtained SEM image is shown in FIG. 4(a). The shape of the microprotrusions was cylindrical with a constant cross-sectional area. Furthermore, the pitch, cross-sectional diameter (inner diameter), and height from the base to the tip of the microprotrusions of antibacterial material 1 were measured by the method described above. Then, the second moment of area and spring constant of the microprotrusions of antibacterial material 1 were calculated based on the following equations (5) and (4). The results are shown in Table 1. I=πD 4 / 64··(5) (In formula (5), I is the second moment of area, and D is the inner diameter of the micro-projection.) k=3EI / L 3 (4) (In formula (4), k is the spring constant, E is the Young's modulus of the material that constitutes the microprojection, L is the height from the base to the tip of the microprojection, and I is the second moment of area of ​​the microprojection.) In addition, a sterilization test was carried out on the antibacterial material 1 by the above-mentioned method, and the viable cell rate was calculated. The viable cell rate is shown in Table 1.

[0104] Example 2 Except for the following changes, an antibacterial material was produced by the same method as in Example 1. This antibacterial material is referred to as antibacterial material 2. In detail, a mold (metal mold) having a nanohole structure was prepared by using a two-stage anodization method (mild anodization), and the antibacterial material was produced by using this mold. The changes were the following (A) and (B) among the conditions described in <Preparation of Mold (Metal Die)> of Example 1. (A) Instead of the first anodization in Example 1, another first anodization is performed to form an oxide film on the Al plate by applying a certain voltage in an acidic electrolyte to the Al plate after the electrolytic polishing treatment as the anode and Pt as the cathode under the conditions shown below. (Conditions for the first anodizing) Applied voltage: 85V, Acid electrolyte type: Oxalic acid Acid electrolyte concentration: 0.3M Acid electrolyte temperature: 0℃ Voltage application time: 15 minutes (B) Instead of the second anodization in Example 1, another second anodization is performed under the following conditions: the Al plate after AAO etching is used as the anode, Pt is used as the cathode, and a certain voltage is applied in an acid electrolyte. (Conditions for the second anodizing) Applied voltage: 85V, Acid electrolyte type: Oxalic acid Acid electrolyte concentration: 0.3M Acid electrolyte temperature: 0℃ Voltage application time: 60 seconds The holes formed in the mold used in Example 2 were cylindrical, with a hole pitch of about 200 nm, a hole diameter of about 100 nm, and a hole depth of about 100 nm.

[0105] The shape of the microprotrusions of the antibacterial material 2 was measured using SEM in the same manner as in Example 1. The obtained SEM image is shown in FIG. 4(b). The shape of the microprotrusions was cylindrical with a constant cross-sectional area. In addition, the pitch, cross-sectional diameter (inner diameter), and height from the base to the tip of the microprotrusions of the antibacterial material 2 were measured in the same manner as in Example 1. Then, the second moment of area and spring constant of the microprotrusions of the antibacterial material 2 were calculated in the same manner as in Example 1. The results are shown in Table 1. The state of the E. coli present on the antibacterial material 2 after the sterilization test was observed using the SEM. The obtained SEM image is shown in FIG. 5.

[0106] In addition, a sterilization test was carried out on the antibacterial material 2 in the same manner as in Example 1, and the viable cell rate was calculated. The viable cell rate is shown in Table 1.

[0107] Comparative Example 1 Except for the changes shown below, an antibacterial material was produced in the same manner as in Example 2. This antibacterial material is designated as Comparative Antibacterial Material 1. The change is that among the conditions described in <Preparation of Mold (Metal Die)> of Example 2, (Conditions for First Anodization) and (Conditions for Second Anodization) were changed to the conditions shown below. (Conditions for the first anodizing) Applied voltage: 40V, Acid electrolyte type: Oxalic acid Acid electrolyte concentration: 0.3M Acid electrolyte temperature: 0℃ Voltage application time: 20h (Conditions for the second anodizing) Applied voltage: 40V, Acid electrolyte type: Oxalic acid Acid electrolyte concentration: 0.3M Acid electrolyte temperature: 0℃ Voltage application time: 60 seconds The holes formed in the mold used in Comparative Example 1 were cylindrical, with a hole pitch of about 100 nm, a hole diameter of about 50 nm, and a hole depth of about 50 nm.

[0108] The shape of the microprotrusions of Comparative antibacterial material 1 was measured using SEM in the same manner as in Example 1. The obtained SEM image is shown in FIG. 4(c). The shape of the microprotrusions was cylindrical with a constant cross-sectional area. In addition, the pitch, cross-sectional diameter (inner diameter), and height from the base to the tip of the microprotrusions of Comparative antibacterial material 1 were measured in the same manner as in Example 1. Then, the second moment of area and spring constant of the microprotrusions of Comparative antibacterial material 1 were calculated in the same manner as in Example 1. The results are shown in Table 1.

[0109] Moreover, a sterilization test was carried out on the comparative antibacterial material 1 in the same manner as in Example 1, and the viable cell rate was calculated. The viable cell rate is shown in Table 1.

[0110] Comparative Example 2 Except for the changes shown below, an antibacterial material was produced in the same manner as in Example 2. This antibacterial material is designated as Comparative Antibacterial Material 2. The changes were that the voltage application time in the second anodization was changed to 15 seconds among the conditions described in <Preparation of Mold (Metal Mold)> in Example 2, and that the shape of the hole was made conical by repeating the second anodization and widening four times each. The shape of the hole formed in the mold used in Comparative Example 2 was cylindrical, with a hole pitch of about 200 nm, a diameter at the top of the hole of about 100 nm, a diameter at the bottom of the hole of about 40 nm, and a hole depth of about 200 nm. The shape of the microprotrusions of Comparative antibacterial material 1 was measured using SEM in the same manner as in Example 1. The obtained SEM image is shown in FIG. 4(d). The shape of the microprotrusions was conical. Furthermore, the pitch, bottom diameter, top diameter, and height from base to tip of the microprotrusions of Comparative antibacterial material 2 were measured in the same manner as in Example 1. Then, the second moment of area and spring constant of the microprotrusions of Comparative antibacterial material 2 were calculated based on the following formulas (6) and (4). The parameters measured and calculated as above are shown in Table 1. I=πD2D1 3 / 64··(6) (In formula (6), I is the second moment of area, D1 is the diameter of the bottom circle, and D2 is the diameter of the top circle.) k=3EI / L 3 (4) (In formula (4), k is the spring constant, E is the Young's modulus of the material that constitutes the microprojection, L is the height from the base to the tip of the microprojection, and I is the second moment of area of ​​the microprojection.) A sterilization test was also conducted on the comparative antibacterial material 2 in the same manner as in Example 1, and the viable cell rate was calculated. The viable cell rate is shown in Table 1. After the sterilization test, the state of E. coli present on the antibacterial material 1 was observed using the SEM. The obtained SEM image is shown in FIG.

[0111] Comparative Example 3 Except for the changes shown below, an antibacterial material was produced in the same manner as in Example 2. This antibacterial material is designated as Comparative Antibacterial Material 3. The changes were that the voltage application time in the second anodization was changed to 15 seconds among the conditions described in <Preparation of Mold (metal mold)> in Example 2, and that the shape of the hole was made conical by repeating the second anodization and widening six times each. The shape of the hole formed in the mold used in Comparative Example 3 was cylindrical, with a hole pitch of about 200 nm, a diameter at the top of the hole of about 100 nm, a diameter at the bottom of the hole of about 40 nm, and a hole depth of about 300 nm.

[0112] The shape of the microprotrusions of Comparative antibacterial material 3 was measured using SEM in the same manner as in Example 1. The obtained SEM image is shown in FIG. 4(e). The shape of the microprotrusions was conical. Furthermore, the pitch, bottom diameter, top diameter, and height from base to tip of the microprotrusions of Comparative antibacterial material 3 were measured in the same manner as in Example 1. Then, the second moment of area and spring constant of the microprotrusions of Comparative antibacterial material 3 were calculated in the same manner as in Comparative Example 2. The results are shown in Table 1.

[0113] Further, a sterilization test was carried out on the comparative antibacterial material 3 in the same manner as in Example 1, and the viable cell rate was calculated. The viable cell rate is shown in Table 1.

[0114] 〔result〕 The physical properties of antibacterial materials 1 and 2 and comparative antibacterial materials 1 to 3 produced in Examples 1 and 2 and Comparative Examples 1 to 3 are shown in Table 1 below. In addition, a graph showing the relationship between the spring constant k of the microprojections of antibacterial materials 1 and 2 and comparative antibacterial materials 1 to 3 and the viable cell rate is shown in Figure 3. [Table 1]

[0115] As shown in Table 1, in Examples 1 and 2, antibacterial materials 1 and 2 were produced in which the spring constant k of the microprojections was 16.2 N / m or more. Therefore, the manufacturing methods of the antibacterial materials described in Examples 1 and 2 correspond to the present manufacturing method, and antibacterial materials 1 and 2 correspond to the present antibacterial material. On the other hand, comparative antibacterial materials 1 to 3 produced in Comparative Examples 1 to 3 have a spring constant k of the microprojections of less than 16.2 N / m. Therefore, the manufacturing methods of the antibacterial materials described in Comparative Examples 1 to 3 do not correspond to the present manufacturing method, and comparative antibacterial materials 1 to 3 do not correspond to the present antibacterial material.

[0116] As shown in Table 1 and FIG. 3, antibacterial materials 1 and 2 have a much lower viable cell rate than comparative antibacterial materials 1 to 3. Therefore, it can be said that antibacterial materials 1 and 2 have a significantly superior antibacterial effect than comparative antibacterial materials 1 to 3. Furthermore, a comparison between FIG. 5 and FIG. 6 shows that antibacterial material 1, which corresponds to the present antibacterial material, deforms the cell membrane of the attached E. coli to a greater extent than comparative antibacterial material 2, which does not correspond to the present antibacterial material. Therefore, it can be said that antibacterial material 1 applies a greater tensile force to the cell membrane than comparative antibacterial material 2, and thus exerts a superior antibacterial effect.

[0117] As described above, according to the present production method, an antibacterial material having an excellent antibacterial effect can be produced. Furthermore, the present antibacterial material has an excellent antibacterial effect. [Industrial Applicability]

[0118] The present manufacturing method can manufacture an antibacterial material having an excellent antibacterial effect. Furthermore, the present antibacterial material has an excellent antibacterial effect. Therefore, the present manufacturing method and the present antibacterial material can be used to manufacture antibacterial components that utilize the antibacterial effect.

Claims

1. 1. A method for producing an antimicrobial material with microprojections, comprising: The spring constant of the microprojection is k=3EI / L. 3 A method for producing an antibacterial material, comprising a step of determining E, I, and L so that E is 16.2 N / m or more (where E is the Young's modulus of a material constituting the microprotrusions, I is the second moment of area of ​​the microprotrusions, and L is the height from the base to the tip of the microprotrusions).

2. The method for producing an antibacterial material according to claim 1 , wherein the shape of the microprojections is one or more selected from the group consisting of a cylinder, a prism, a cone, and a pyramid.

3. The method for producing an antibacterial material according to claim 2 , wherein the shape of the microprojections is one or more selected from the group consisting of cylinders, cones and prisms.

4. The method for producing an antibacterial material according to any one of claims 1 to 3, further comprising the step of coating the surface of the microprojections with an inorganic material.

5. 1. An antimicrobial material comprising microprojections, The spring constant of the microprojection is k=3EI / L. 3 An antibacterial material in which E, I, and L are controlled so that E is 16.2 N / m or more (wherein E is the Young's modulus of the material constituting the microprotrusions, I is the second moment of area of ​​the microprotrusions, and L is the height from the base to the tip of the microprotrusions).

6. The antimicrobial material of claim 5 , wherein the shape of the microprojections is one or more selected from the group consisting of cylinders, prisms, cones, and pyramids.

7. The antimicrobial material of claim 6 , wherein the shape of the microprojections is one or more selected from the group consisting of a cylinder, a cone, and a prism.

8. The antibacterial material according to any one of claims 5 to 7, wherein the surface of the microprojections is coated with an inorganic material.

Citation Information

Patent Citations

  • Method for producing antifouling film

    JP2019064056A

  • Antibacterial material, and antibacterial component including the same

    JP2019072475A